Planning for Building Digital Memory of the Sudan “DMS” - Ghobrial, Rafaa; Sharif, Sami (My University, 2010)
Advances in information and communication technologies led to the emerging of modern digital systems which facilitate sharing and preservation of information and innovations. These systems are thus supportive of the cultural "collective" memory of the nation, a local repository of explicit and tacit knowledge. This paper aims to study the digital systems that help to secure and improve the reliability of memory of the Sudanese nation with the transfer of information and communication technology from perceptions of the users. This paper has reviewed and assessed infrastructures, resources, systems and ICT readiness which will contribute to building the Digital Memory of Sudan. The outputs guide running reforms and rehabilitation, building capacity and revitalizing the infrastructure of the digital environment, which affects reliability and shared resources in memory institutions. It is concluded that memory institutions are a repository of Sudanese intangible and tangible content which will be represented in the Digital Memory of Sudan. Finally the paper proposes to revitalize the country's cultural policies in line with the principles of cultural diversity and development of a comprehensive strategy for long-lived digital explicit and tacit knowledge.
Keywords: ICADLA, conference, digital library, archive, Sudan, DMS